The effect of helium–oxygen‐assisted mechanical ventilation on chronic obstructive pulmonary disease exacerbation: A systemic review and meta‐analysis. (14th June 2017) - Wu, Xu; Shao, Chuan; Zhang, Liang; Tu, Jinjing; Xu, Hui; Lin, Zhihui; Xu, Shuguang; Yu, Biyun; Tang, Yaodong; Li, Shanqun
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is often accompanied by acute exacerbations. Patients of COPD exacerbation suffering from respiratory failure often need the support of mechanical ventilation. Helium–oxygen can be used to reduce airway resistance during mechanical ventilation. The aim of this study is to evaluate the effect of helium–oxygen‐assisted mechanical ventilation on COPD exacerbation through a meta‐analysis. Methods: A comprehensive literature search through databases of Pub Med (1966∼2016), Ovid MEDLINE (1965∼2016), Cochrane EBM (1991∼2016), EMBASE (1974∼2016) and Ovid MEDLINE was performed to identify associated studies. Randomized clinical trials met our inclusion criteria that focus on helium–oxygen‐assisted mechanical ventilation on COPD exacerbation were included. The quality of the papers was evaluated after inclusion and information was extracted for meta‐analysis. Results: Six articles and 392 patients were included in total. Meta‐analysis revealed that helium–oxygen‐assisted mechanical ventilation reduced Borg dyspnea scale and increased arterial PH compared with air–oxygen. No statistically significant difference was observed between helium–oxygen and air–oxygen as regards to WOB, PaCO2, OI, tracheal intubation rates and mortality within hospital. Conclusions: Our study suggests helium–oxygen‐assisted mechanical ventilation can help to reduce Borg dyspnea scale. In terms of the tiny change of PH, its clinical benefit is negligible. There is no conclusive evidence indicating the beneficial effect of helium–oxygen‐assisted mechanical ventilation on clinical outcomes or prognosis of COPD exacerbation.